Real-World Effectiveness of Palbociclib Plus Letrozole vs Letrozole Alone for Metastatic Breast Cancer With Lung or Liver Metastases: Flatiron Database Analysis - Brufsky, Adam; Liu, Xianchen; Li, Benjamin; McRoy, Lynn; Layman, Rachel M. (Frontiers in Oncology, 2022)
Background: Cyclin-dependent kinase 4/6 inhibitors are a standard treatment for patients with hormone receptor−positive (HR+)/ human epidermal growth factor receptor 2−negative (HER2−) metastatic breast cancer (MBC). However, real-world data on effectiveness in patients with liver or lung metastatic disease is limited. This study compared outcomes of palbociclib plus letrozole versus letrozole alone in patients with HR+/HER2− MBC with lung or liver metastasis treated in routine clinical practice in the United States. Methods: This retrospective analysis used Flatiron Health’s database of electronic health records. Women with HR+/HER2− MBC and liver or lung metastasis received first-line palbociclib plus letrozole or letrozole alone between February 2015 and February 2019. Real-world progression-free survival (rwPFS) was defined as time from start of treatment to death or disease progression. Stabilized inverse probability treatment weighting was used to balance baseline demographic and clinical characteristics between palbociclib plus letrozole versus letrozole cohorts. Cox proportional-hazards models were used to estimate the effectiveness of palbociclib plus letrozole versus letrozole alone in rwPFS and overall survival (OS). Results: The study included 353 patients with lung metastasis, 123 with liver metastasis, and 75 with both. After adjusting for baseline demographics and clinical characteristics, palbociclib plus letrozole compared with letrozole alone demonstrated a median rwPFS of 16.5 versus 10.5 months, respectively (hazard ratio, 0.52; P<0.001), a median OS not reached versus 40.3 months (hazard ratio, 0.60; P<0.01) in patients with lung metastasis, and median OS of 30.1 vs 16.8 months (hazard ratio, 0.56; P<0.03 in patients with liver metastasis. In patients with liver metastasis, palbociclib plus letrozole had a median rwPFS of 10.7 months versus 8.0 months in the letrozole alone cohort (hazard ratio, 0.70; P=0.12). Conclusions: In this real-world population, palbociclib in combination with letrozole is associated with improved outcomes compared with letrozole alone for patients with HR+/HER2− MBC and liver or lung metastasis in the first-line setting. The findings support first-line palbociclib in combination with an aromatase inhibitor as standard of care for HR+/HER2− MBC regardless of visceral disease.